Cortical Activity During an Attack of Ménière's Disease—A Case Report - Devantier, Louise; Hansen, Allan K.; Mølby-Henriksen, Jens-Jacob; Pedersen, Michael; Borghammer, Per; Ovesen, Therese; Magnusson, Måns (Frontiers in Neurology, 2021)
Background: Ménière's disease (MD) is a chronic peripheral vestibular disorder with recurrent episodes of vertigo accompanied by fluctuating hearing loss, tinnitus and aural fullness in the affected ear. There are several unanswered fundamental questions regarding MD, one of these being cortical activity during a MD attack. However, it is not possible to plan an investigation in an episodic disease as MD. Objective: To visualize cortical activity during an attack of MD. Method:18F-FDG PET scans were used to visualize cortical activity in a 62 years old male suffering from definite MD. Two 18F-FDG PET scans were performed. One to show activity during the attack and one to show normal baseline brain activity 7 days after the attack. Results: A number of low-magnitude fluctuations in the 18F-FDG FDG uptake were found in 18F-FDG PET examination following the MD attack compared to the patient's own baseline 18F-FDG FDG scan. Across both hemispheres no significant changes were seen. However, reduced activity was observed in most of the orbitofrontal, frontal cortices as well as Heschl's gyrus and insula. Conclusion: This is the first neuroimaging showing alteration of brain activity during an attack in a patient with MD. No strong focal alterations was seen. It is noteworthy that the decreased activity observed was in the insula and Heschl's gyrus that seems to be core areas for processing information from the labyrinth. It is also of interest that decreased activity rather than hyperactivity was observed.